2012
DOI: 10.1038/ejhg.2012.47
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analyses of genome-wide linkage scans of anxiety-related phenotypes

Abstract: Genetic factors underlying trait neuroticism, reflecting a tendency towards negative affective states, may overlap genetic susceptibility for anxiety disorders and help explain the extensive comorbidity amongst internalizing disorders. Genome-wide linkage (GWL) data from several studies of neuroticism and anxiety disorders have been published, providing an opportunity to test such hypotheses and identify genomic regions that harbor genes common to these phenotypes. In all, 11 independent GWL studies of either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…For AD, similar analysis using a smaller set of samples found suggestive evidence for linkage on chromosomes 1, 5, 15, and 16. The results for AD and neuroticism were moderately but significantly correlated …”
Section: Molecular Geneticsmentioning
confidence: 84%
See 1 more Smart Citation
“…For AD, similar analysis using a smaller set of samples found suggestive evidence for linkage on chromosomes 1, 5, 15, and 16. The results for AD and neuroticism were moderately but significantly correlated …”
Section: Molecular Geneticsmentioning
confidence: 84%
“…conducted linkage analyses of phobic disorder in a set of pedigrees ascertained for PD and reported linkage on chromosome 3q for agoraphobia, 14q for specific phobia, and 16q for social phobia . A recent meta‐analysis of all available genome‐wide linkage studies of anxious temperament (neuroticism) using eight independent samples with over 14 000 subjects supported linkage on chromosomes 9, 11, 12, and 14 . For AD, similar analysis using a smaller set of samples found suggestive evidence for linkage on chromosomes 1, 5, 15, and 16.…”
Section: Molecular Geneticsmentioning
confidence: 94%
“…Genes and environmental factors influence the occurrence of both lefthandedness and mental health disorders. Genes implicated in anxiety and depression include the following: CRHR1, the Corticotropin Releasing Hormone Receptor-1, 5-HTTLPR, the 5-HydroxyTryptamine (serotonin) Transporter Gene-Linked Polymorphic Region gene, and BDNF, the brain-derived neurotropic factor gene, among others (Boulle et al, 2012;Rogers et al, 2013;Webb et al, 2012). Environmental factors, such as maltreatment and violence exposure, also place individuals at higher risk for the development of depression, anxiety and posttraumatic stress (Anda et al, 2007;Rogers et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that both dopamine and serotonin partially exert their actions by modulating the activity of AKT [42], [43]. Furthermore, chromosome 4q32 region was suggested to be associated with ADs (PD, SAD, and phobia) in a previous linkage study [44], although this region was not confirmed in a recent meta-analysis of linkage data for ADs [45].…”
Section: Discussionmentioning
confidence: 94%